MODERASI BERAGAMA DAN PERAN GURU DALAM PENANAMANNYA DI SEKOLAH - Darma Yanti, Annisa; Masduki; Syafiuddin, Fauzan Azima; Siregar, Syahruddin (UIN Sunan Kalijaga Yogyakarta, 2024)
Indonesia is a country with all the diversity that exists. Ethnic, cultural and religious diversity are some of the forms of diversity that exist in Indonesia. Prolonged conflicts in the name of religion often occur in various regions in Indonesia. Mosques are burned, churches are attacked, religious leaders are subjected to cruelty by irresponsible hands, suicide bombings in the name of religion, radicalism and discrimination in the name of sara issues often occur and become national news. For this reason, an attitude or perspective is needed to be a resolution to the conflict. Religious moderation is a moderate perspective, attitude and behavior in religion, namely understanding and practicing religious teachings without extremes. Neither extreme right nor extreme left. Basically, normative Islam itself has a wasathiyah character, moderation. Religious moderation education in strengthening national insight is important especially in recent years the diversity on earth Indonesia is being tested by the existence of extreme religious attitudes expressed by a group of people in the name of religion. This happens in actions in the real world and statements in cyberspace. This exclusive and intolerant group is dangerous for the religious climate in Indonesia. This research is a type of library research. What is called library research or often also called library studies, is a series of activities using library data collection methods, reading and recording and processing research materials. The world of education is the foundation of hope for strengthening the values of religious moderation. The high participation of the Indonesian people in establishing and organizing religion-based educational institutions needs to be directed to strengthen this idea. Religious moderation education needs to be developed along with the character building of students. Religious moderation education is expected to answer the target of the mental revolution of students to continue to develop the values of peace and tolerance. Keywords : Religious Moderation, Teacher Role, School Indonesia merupakan negara dengan segala keragaman yang ada. Keragaman suku bangsa, budaya dan agama merupakan beberapa bentuk keberagaman yang ada di Indonesia. Konflik berkepanjangan atas nama agama sering kali terjadi di berbagai daerah di Indonesia. Masjid dibakar, Geraja diserang, tokoh agama menjadi sasaran kekejaman tangan-tangan tidak bertanggung jawab, bom bunuh diri mengatasnamakan agama, radikalisme dan diskriminasi atas nama isu sara seringkali terjadi dan menjadi pemberitaan nasional. Untuk itu dibutuhkan suatu sikap atau cara pandang untuk dapat menjadi resolusi dari konflik tersebut. Moderasi beragama merupakan cara pandang, sikap dan perilaku dalam beragama secara moderat, yakni memahami dan mengamalkan ajaran agama dengan tidak ekstrem. Baik ekstrem kanan maupun ekstrem kiri. Pada dasarnya normatif Islam itu sendiri mempunyai watak wasathiyah, moderasi. Pendidikan moderasi beragama dalam penguatan wawasan kebangsaan menjadi penting apalagi dalam beberapa tahun terakhir keragaman di bumi Indonesia sedang diuji dengan adanya sikap keberagamaan yang ekstrem yang diekspresikan oleh sekelompok orang yang mengatas namakan agama. Hal ini terjadi dalam aksi-aksi di dunia nyata maupun statement di dunia maya. Kelompok ekslusif dan intoleran ini membahayakan bagi iklim keberagamaan di Indonesia. Penelitian ini merupakan sebuah penelitian dengan jenis riset kepustakaan. Apa yang disebut dengan riset kepustakaan atau sering juga disebut studi pustaka, merupakan serangkaian kegiatan yang dengan metode pengumpulan data pustaka, membaca dan mencatat serta mengolah bahan penelitian. Dunia pendidikan menjadi tumpuan harapan untuk penguatan kembali nilai-nilai moderasi beragama. Partisipasi masyarakat Indonesia yang tinggi dalam mendirikan dan menyelenggarakan lembaga pendidikan berbasis agama, perlu diarahkan untuk menguatkan gagasan ini. Pendidikan moderasi beragama perlu dikembangkan beriringan dengan pembangunan karakter peserta didik. Pendidikan moderasi beragama diharapkan menjawab sasaran revolusi mental para peserta didik untuk terus mengembangkan nilai-nilai kedamaian dan toleransi. Kata kunci : Moderasi Beragama, Peran Guru, Sekolah